USING SPORTS GAMES TO DEVELOP YOUNG PLAYERS' SPORTS SKILLS - Ismatov, Abdukodir (Журнал иностранных языков и лингвистики, 2024)
This article explores the effectiveness of using sports games as a key strategy in developing young players' physical, cognitive, and tactical skills. It emphasizes how game-based learning fosters essential abilities such as speed, endurance, coordination, teamwork, and strategic thinking. Unlike traditional drills, sports games provide an engaging and enjoyable environment, encouraging athletes to stay motivated and committed to long-term development. The role of coaches is highlighted, focusing on how they design purposeful games, provide feedback, and nurture reflective learning. This article argues that sports games are essential tools not only for enhancing athletic skills but also for promoting emotional resilience, teamwork, and leadership qualities in young athletes.